(untitled) (Damascus University Journal of agriculture sciences, 2025)
This research was conducted at Agriculture Engineering Faculty, Food Science Department, and Directorate Labs of Interior Traded Minister during the year of 2021 to study some chemical and physical properties of three kinds of honey bees (Yanson, Hallap and Mrer) produced in Damascus Countryside and the effect of heat treatments (40, 50 and 70 C◦) with incubation time (24, 48 and 72 hr) on hydroxy methyl furfural (HMF) production by using liquid chromatography (HPLC). Results revealed that some chemical and physical properties were affected by climate factor, region, honey harvest season and storage conditions. The effect of heat treatments on HMF was in average of 25.4 mg/kg for Yanson, 28.4 mg/kg for Halap and 27.3 mg/kg for Mrer before heat treatments, and stayed under the limits when incubating the samples for 24 hr under temperature of 70 C◦ with average of 32.3, 34.3 and 36.3 mg/kg for honeybee of yanson, Hallap and Mrer respectively. Then, there was slow changing when incubating samples for 48 hr under temperature of 70 C◦ with average 0f 37.33, 39.5 and 40 mg/kg for Yanson , Hallap and Mrer respectively. Whereas, incubation time for 72 hr the total HMF was reached the limits of Syrian standard (40 mg/kg) under the temperature of 70 C◦ for all studied samples.